Pro Bono Lembaga Bantuan Hukum (LBH) XYZ and Partners : Analisis Pendekatan Business Model Canvas (BMC) - Napis Qurtubi, Achmad; Hamka Lubis, Rusdi (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2024)
This study aims to analyze the implementation of the Business Model Canvas (BMC) at LBH XYZ and Partners, a legal aid organization affiliated with a leading private Islamic university in Indonesia. The LBH is committed to a social mission of providing pro bono legal services to underserved communities, particularly vulnerable groups. By adopting the BMC framework, the organization can map out key operational elements such as customer segments, value propositions, channels, customer relationships, and cost structures. The study's findings indicate that the application of BMC enables LBH to enhance its operational effectiveness and efficiency, particularly in identifying and serving the appropriate customer segments and in formulating a value proposition aligned with its social mission. However, challenges such as limited human resources with a deep understanding of BMC and the adaptation of this business model to a non-profit context need to be addressed. With proper training and model adjustments, BMC can be an effective tool for improving the performance of LBH, ensuring sustainability, and creating a more significant impact on society.